Mercury toxicokinetics of the healthy human term placenta involve amino acid transporters and ABC transporters. (18th January 2016) - Straka, Elisabeth; Ellinger, Isabella; Balthasar, Christina; Scheinast, Matthias; Schatz, Jasmin; Szattler, Tamara; Bleichert, Sonja; Saleh, Leila; Knöfler, Martin; Zeisler, Harald; Hengstschläger, Markus; Rosner, Margit; et al.
Highlights: It is known that MeHg is able to pass the placenta and to affect fetal brain development. Uptake and efflux transporters were examined in human primary trophoblast cells and BeWo cells. Involvement in mercury transfer was assessed by measurement of cellular mercury content upon siRNA mediated gene knockdown. Localization of transporters was determined by immunofluorescence microscopy. LAT1 and rBAT at the apical membrane of the syncytiotrophoblast (STB) are involved in MeHg uptake. MRP1 located at basal membrane of STB mediates mercury efflux. Abstract: Background: The capacity of the human placenta to handle exogenous stressors is poorly understood. The heavy metal mercury is well-known to pass the placenta and to affect brain development. An active transport across the placenta has been assumed. The underlying mechanisms however are virtually unknown. Objectives: Uptake and efflux transporters (17 candidate proteins) assumed to play a key role in placental mercury transfer were examined for expression, localization and function in human primary trophoblast cells and the trophoblast-derived choriocarcinoma cell line BeWo. Methods: To prove involvement of the transporters, we used small interfering RNA (siRNA) and exposed cells to methylmercury (MeHg). Total mercury contents of cells were analyzed by Cold vapor-atomic fluorescence spectrometry (CV-AFS). Localization of the proteins in human term placenta sections was determined via immunofluorescence microscopy. Results: We found the amino acid transporter subunits L-type amino acid transporter (LAT)1 and rBAT (related to b 0, + type amino acid transporter) as well as the efflux transporter multidrug resistance associated protein (MRP)1 to be involved in mercury kinetics of trophoblast cells ( t -test P < 0.05 ). Conclusion: The amino acid transporters located at the apical side of the syncytiotrophoblast (STB) manage uptake of MeHg. Mercury conjugated to glutathione (GSH) is effluxed via MRP1 localized to the basal side of the STB. The findings can well explain why mercury is transported primarily towards the fetal side.